2019
DOI: 10.1029/2018ja026160
|View full text |Cite
|
Sign up to set email alerts
|

Particle Beams in the Vicinity of Magnetic Separatrix According to Near‐Lunar ARTEMIS Observations

Abstract: We study characteristics of ion and electron beams observed during 101 crossings of the near-separatrix region by Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) spacecraft in the magnetotail. We found that accelerated ion beams are observed under any level of geomagnetic activity. A duration of earthward moving ion beams is statistically longer (≤ 10 min) than a duration of tailward ion beams (≤ 4 min), which can be due to the transient character of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Before 0419 UT the electron density is low (e) and spacecraft potential is large-(f) with indications that electron density dropped down by a factor 2 below its lobe values between 0418 and 0419 UT. Maximal parallel energy of accelerated electrons ∼500 eV was attained at ∼0418:20 (c), such rather low value is typical for distant reconnection events observed tailward of lunar orbit (Grigorenko et al, 2019). Energy-dispersed energetic proton beam developed since 0418:10 UT (h) and the gradual increase of electron density was observed (e).…”
Section: Two Examples Of Distant Crossingsmentioning
confidence: 98%
“…Before 0419 UT the electron density is low (e) and spacecraft potential is large-(f) with indications that electron density dropped down by a factor 2 below its lobe values between 0418 and 0419 UT. Maximal parallel energy of accelerated electrons ∼500 eV was attained at ∼0418:20 (c), such rather low value is typical for distant reconnection events observed tailward of lunar orbit (Grigorenko et al, 2019). Energy-dispersed energetic proton beam developed since 0418:10 UT (h) and the gradual increase of electron density was observed (e).…”
Section: Two Examples Of Distant Crossingsmentioning
confidence: 98%
“…It is then exposed not to the solar wind but to the terrestrial magnetotail plasma environment, offering the possibility to study in-situ magnetotail dynamics and its dependence on solar and geomagnetic activity (e.g., Kallio and Facskó, 2015;Kallio et al, 2019). Phenomena such as plasmoids released from the near-Earth magnetotail and propagating anti-Sunward, hot plasma flows, energetic particle bursts, plasma waves, magnetic reconnection and plasma sheet dynamics can thus be studied in-situ (e.g., Parks et al, 2001;Nakamura, 2006;Taylor et al, 2006;Nagai et al, 2009;Du et al, 2011;Artemyev et al, 2017;Grigorenko et al, 2019;Sitnov et al, 2019;Kronberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Grigorenko et al. (2019) studied ion and electron beams observed by the ARTEMIS probes near the plasma sheet boundary layer (PSBL). They found no significant differences in characteristics between earthward and tailward ion beams, nor between beams observed on open or closed field lines.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that typical ion energy spectra obtained in the outflows are characterized by increased fluxes at energies above 10 keV compared to the ion spectra in the background plasma sheet, while the spectral shape was non-Maxwellian with a pronounced high energy tail. Grigorenko et al (2019) studied ion and electron beams observed by the ARTEMIS probes near the plasma sheet boundary layer (PSBL). They found no significant differences in characteristics between earthward and tailward ion beams, nor between beams observed on open or closed field lines.…”
mentioning
confidence: 99%